Blockade of RAGE in Zucker obese rats with experimental periodontitis. (12th March 2016) - Grauballe, M. B.; Østergaard, J. A.; Schou, S.; Flyvbjerg, A.; Holmstrup, P.
Abstract : Background and Objective: Periodontitis and type 2 diabetes mellitus (T2D) are two interrelated chronic diseases. Periodontitis is more prevalent in patients with T2D than in healthy subjects, and studies indicate that periodontitis impacts the metabolic control of patients with T2D. Hyperglycemia in T2D leads to the formation of advanced glycation end‐products (AGEs). Binding of AGEs to the receptor of AGE (RAGE) elicits an increased inflammatory response that may be a key modulator linking the two diseases. The present study aimed to elucidate the effect of blocking the RAGE on the interrelationship between periodontitis and T2D in a rat model of both diseases. Material and methods: Zucker obese rats (HsdHlr:ZUCKER‐ Lepr fa/fa ) and their lean littermates were divided into five treatment groups, with and without periodontitis. Monoclonal anti‐RAGE IgG3 were injected into the rats three times a week. The diabetic state was evaluated by oral glucose tolerance tests (OGTTs), the homeostasis model assessment (HOMA), concentration of free fatty acids and repeated measurements of blood glucose. Markers of systemic inflammation, including interleukin (IL)‐1β, IL‐6 and tumor necrosis factor α, were evaluated in plasma. Kidney complications were evaluated by quantitative real‐time PCR, the creatinine clearance rate, the albumin excretion rate and kidney hypertrophy. Periodontitis was evaluated by morphometric registration of alveolar bone loss and radiographic recording of bone support. Results: The diabetic state was improved by antibody treatment for 4 wk, resulting in a lower area under the glucose concentration curve during OGTTs, lower insulin levels and a lower HOMA. Furthermore, the antibody treatment resulted in milder kidney complications, as evaluated by measuring the albumin excretion rate and the kidney weight. There was no impact of periodontal inflammation on the level of complications. Periodontal bone support was influenced by diabetes, but the altered diabetic status as a result of treatment with anti‐RAGE Ig had no effect on periodontitis. Conclusion: In this study, treatment with anti‐RAGE IgG3 resulted in improved glucose tolerance and attenuated renal complications. However, no effect was observed on the diabetes‐associated periodontitis in Zucker obese rats. Furthermore, periodontitis had no effect on diabetic markers or renal complications. Therefore, activation of RAGE is important in the development of T2D.